GAME SCORING SUPPORTING OBJECTS MENGGUNAKAN AGEN CERDAS BERBASIS ARTIFICIAL INTELLIGENCE - Astrid Novita Putri; Rastri Prathivi (Jurusan Teknologi Informasi Universitas Semarang, 2016)
Game are activity most structure, one that ordinary is done in fun and also education tool and help to develop practical skill, as training, education, simulation or psychological. On its developing current game have until 3D. In one game, include in First Person Shutter necessary scoring one that intent to motivate that player is more terpacu to solve game until all through, on scoring Super Mario's game Boss, Compass does count scoring haven't utilized Artifical Intelligent so so chanted, while player meet with supporting objects example ammor ability really guns directly dead, so is so easy win. Therefore at needs a count scoring interesting so more motivated in finishing problem Scoring accounting point for First Person Shutter's game .This modelling as interesting daring in one game, since model scoring one that effective gets to motivate that player is more terpacu in plays and keep player for back plays. Besides model scoring can assign value that bound up with game zoom.On Research hits scoring this game will make scoring bases some criterion which is health Point, Attack point, Defence point, And Magic what do at have supporting objects ,then in this research do compare two method are methodic statistic and Fuzzy. Result of this research 83,4 % on testing's examination and on eventually gets to be concluded that fuzzy's method in trouble finish time more long time but will player more challenging to railroad.